The Effect of Search, Solve, Create, Share (SSCS) Learning Model on Scientific Reasoning Ability - Muhammad Amin Nasir; Adieba Warda Hayya (Bioeduca : Journal of Biology Education, 2023)
The purpose of this study was to determine the effect of the Search, Solve, Create, and Share (SSCS) learning model on students' scientific reasoning abilities in the material of the human movement system. The method used in this research is quasi-experimental. This study used two experimental classes with the SSCS model and a control class with the conventional model. Data were obtained through observation techniques, student response questionnaires, and scientific reasoning ability tests. The results of the study stated that the SSCS model had an effect on students' scientific reasoning abilities. The results of the hypothesis test stated that H0 was rejected and Ha was accepted. This is based on the results of hypothesis testing using the Mann-Whitney test which obtains an Asymp value. Sig. (2-tailed) 0,000 0,05. Through this research, it was revealed that the SSCS learning model had an effect on students' scientific reasoning abilities.